2016
DOI: 10.1200/jgo.2015.003079
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Reporting in Lagos, Nigeria: Implications for Training and Education in Africa

Abstract: PurposeTo assess the completeness and accuracy of breast cancer pathologic reporting in Nigeria.Materials and MethodsThe histologic parameters provided in breast cancer pathology reports at a large teaching hospital in Nigeria were assessed. The corresponding slides were reviewed after the United Kingdom Royal College of Pathologists guidelines, and results were compared.ResultsOut of 115 breast cancer cases, histologic type of breast carcinoma was concordant with the review type in 53.1% of cases and discorda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 15 publications
2
21
1
Order By: Relevance
“…Audits of breast cancer pathology reports in Nigeria from 1999 to 2008 21 and from 2011 to 2013 22 also described incomplete reporting of recommended pathology information. Atanda and Atanda 21 noted that their laboratory was “at a stage comparable to that in most laboratories in Australia in 1995 before the release of specific recommendations for breast cancer reporting,” and Daramola et al 22 recommended adoption of synoptic reporting, stating that, “The use of proformas, with the inclusion of all the main parameters, would ensure adequacy of reports.”…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Audits of breast cancer pathology reports in Nigeria from 1999 to 2008 21 and from 2011 to 2013 22 also described incomplete reporting of recommended pathology information. Atanda and Atanda 21 noted that their laboratory was “at a stage comparable to that in most laboratories in Australia in 1995 before the release of specific recommendations for breast cancer reporting,” and Daramola et al 22 recommended adoption of synoptic reporting, stating that, “The use of proformas, with the inclusion of all the main parameters, would ensure adequacy of reports.”…”
Section: Discussionmentioning
confidence: 99%
“…Although quite a few studies have evaluated the completeness of breast cancer pathology reports in high-resource settings over the past three decades, 5 , 16 - 20 to the best of our knowledge, only two published reports described similar audits in sub-Saharan Africa. 21 , 22 Both of these studies identified substantial gaps in documentation of BHGI basic pathology information. 12 - 14 …”
Section: Introductionmentioning
confidence: 99%
“…Although hard data are rare, several papers have examined some of the issues. A retrospective assessment of reports of breast carcinoma in the university teaching hospital in Lagos, Nigeria in 2016, showed that 60% of the reports did not mention lymph node status and 50% did not mention excision margins [6]. Hormone receptor was not stated in 74% cases.…”
Section: Standardsmentioning
confidence: 99%
“…Although Nigeria is one of the few African countries that have published guidelines, created by the Nigeria Breast Pathology Working Group in 2010, on standardized pathology reporting, these guidelines have not been adequately circulated or implemented in medical centers. Daramola et al 69 compared histologic parameters in pathology reports from a teaching hospital in Nigeria with the cancer data set of the Royal College of Pathologists in the United Kingdom to verify compliance and concordance. Almost half of the Nigerian BC cases examined were discordant with the Royal College of Pathologists, and roughly half of the cases were either undergraded or overgraded.…”
Section: Adding Fuel To the Fire: Challenges In Tnbc Care And Treatmementioning
confidence: 99%